Entre a autonomia e a complacência: imbricamentos do processo de gestão e das manifestações da desproteção social no trabalho sob ordem - Costa, Raquel Cristina Serranoni da (2019)
The hierarchically driven institutional work is necessarily an under-orders job that initially has assignments, objectives, and goals and, a modus operandi defined according to the professional’s actions. This study proceeds - through the author’s professional ego-history - with the documental analysis of social assistance services provided to families – PAIF - Serviço de Proteção e Atendimento Integral à Família (A Brazilian entity which provides protection and full time servisse to families in need of social protection). This study also carries out an inductive process of the research that has empirically explored dialogue with seven professionals - workers and middle managers. It has been analyzed in this dialogue: the relation of under-orders professional work and its professionals with the service’s subjects - the users - under the light of the attention processes they operate on. The analysis happens at PAIF and took place at four CRAS - Centros de Referência de Assistência Social (Centers for Social Assistance and Reference) located at a given middle size town and it is based on the certainty that social assistance in Brazil is a public policy regulated by SUAS, which through their attentions, make social assistance rights real. It is proposed in this work the characterization of operative patterns expressed on the very tense work relation between the social assistant and the institutionalized work (under-orders) which ends up imbricating the management processes whit sing and collective manifestations of lack of social protection. The revelations reached by the analysis of this research’s empirical content, present the four perspectives that have stood out for the under-orders job: seized amount of time, planning as a collective pact, the proximity to the subject’s daily routine and, the worker and the service’s reference